Towards achieving the goal for early childhood and care education in global education for all (EFA) (2013)
The multiple benefits that early childhood and care education has on children for their nutrition, health and educational development and the role of high quality programmes on offsetting disadvantage and inequality has been recognized in recent times. This therefore explains why the rate of development of any nation is closely tied to early childhood and care education. Yet the enormous influence that early childhood and care education has on children and national development is far from being realized as envisaged. This paper therefore focuses on the first Education for All (EFA) goals, which deal with expanding and improving comprehensive early childhood care and education. The paper, also mentions the constraints hindering its achievement and suggests ways by which the goal can be achieved.